Invasive haemodynamic assessment in heart failure with preserved ejection fraction - Phuuwadith Wattanachayakul; Veraprapas Kittipibul; Husam M. Salah; Hidenori Yaku; Finn Gustafsson; Claudia Baratto; Sergio Caravita; Marat Fudim (ESC Heart Failure)
Abstract Despite the increasing prevalence and substantial burden of heart failure with preserved ejection fraction (HFpEF), which constitutes up to 50% of all heart failure cases, significant challenges persist in its diagnostic and therapeutic strategies. These difficulties arise primarily from the heterogeneous nature of the condition, the presence of various comorbidities and a wide range of phenotypic variations. Considering these challenges, current international guidelines endorse the utilization of invasive haemodynamic assessments, including resting and exercise haemodynamics, as the gold standard for enhancing diagnostic accuracy in cases where traditional diagnostic methods yield inconclusive results. These assessments are crucial not only for confirming the diagnosis but also for delineating the complex underlying pathophysiology, enabling the development of personalized treatment strategies, and facilitating the precise classification of HFpEF phenotypes. In this review, we summarize the haemodynamic changes observed in patients with HFpEF, comparing resting and exercise‐induced parameters to those of normal subjects. Additionally, we discuss the current role of invasive haemodynamics in HFpEF assessment and highlight its utility beyond diagnosis, such as identifying HFpEF comorbidities, guiding phenotype‐based personalized therapies and characterizing prognostication. Finally, we address the challenges associated with utilizing invasive haemodynamics and propose future directions, focusing on integrating these assessments into routine HFpEF care.